Effect of diet-induced weight loss on cytokeratin-18 levels in overweight and obese patients with liver fibrosis. Issue 2 (March 2019) - Safarian, Mohammad; Mohammadpour, Sepideh; Shafiee, Mojtaba; Ganji, Azita; Soleimani, Anvar; Nematy, Mohsen; Bahari, Ali
Abstract: Aims: Liver biopsy is currently the gold standard test for NAFLD diagnosis and staging but has many drawbacks. In addition, other tools such as transient elastography are limited to specialized research centers. To assess the usefulness of CK-18 as a non-invasive biomarker for detecting therapeutic responses in patients with liver fibrosis. Materials and methods: Sixty overweight and obese patients with liver fibrosis were evaluated by a dietitian and given a weight-reducing diet with a calorie deficit of 500–1000 kcal/day over a 6-month period. Controlled attenuation parameter (CAP) and liver stiffness measurement (LSM) both were performed at the beginning and at the end of the trial to determine liver steatosis and liver fibrosis, respectively. Serum CK-18 levels were measured by enzyme linked immune sorbent assay (ELISA) at baseline and at 3 and 6 months after intervention. Results: Patients experienced a rapid weight loss of −7.6 kg (8.5%) during the trial. Among all participants, liver steatosis decreased from 76.5 ± 12.2% to 51.8 ± 24.4% (baseline to end-point) (p < 0.001) and fibrosis score decreased from 9.9 ± 3.7 to 7.2 ± 2.4 (p < 0.001) (a 27.2% decrease). Serum CK-18 levels decreased from 290.2 ± 98.1 U/L to 217.6 ± 64.8 U/L (p < 0.001) (a 25.0% decrease). ΔCK-18 was found to be significantly associated with delta fibrosis score (r = 0.25, p = 0.05) Conclusions: This trial showed a significant positive association between changes in CK-18 levels and changes in liver fibrosis over a 6-month dietary intervention